Hubungan antara Knowledge-Technology-Innovation (KTI), Commitment, Competence, Leadership, Government Policy, Human Capital, dan Competitive Advantage - Darjat Sudrajat (Binus Business Review, 2014)
In current tight competitive situation, companies always try to create differentiation anytime to achieve better and sustainable performance. Rapid and unpredictable changes insist the companies should always be innovative, so that aspects of globalization, e-business, technology innovation, creativity, global competition, knowledge creation, diffusion of new technologies and knowledge revolution should be sources of performance and competitiveness improvement. Therefore, tomaintain core competencies and competitive advantage, the companies should develop continuous innovation, technologylearning, and knowledge management. Knowledge-Technology-Innovation (KTI) can be a driver for country’s development and growth. Japan, South Korea, and Singapore are the countries that have limited natural and human resources, but able to achieve sustainable economic development. KTI is not only to be practiced at individual and organizational level, but also can be implemented at the community, national, or state level. KTI, therefore, can encourage expected competitive advantage creation and become a decisive factor for a country to achieve stable and sustainable economic growth. This research intends to analyze relationships of KTI, competitive advantage, commitment, leadership, human capital, government policy,and competence. This research used correlational method and literature study approach. The result of this research is a relationship model of each of these aspects that can be used as a framework for further research. The relationships model isas follows: Leadership, competence, and human capital (as independent variables) have direct relationship (influence) oncompetitive advantage (dependent variable) or indirectly (through KTI as an intervening variable); KTI has direct relationship (effect) on competitive advantage; Government policy and commitment are moderator variables for relationshipof KTI and competitive advantage.